2006
DOI: 10.1007/s10546-006-9103-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of mixing height and dust concentration with lidar ceilometer

Abstract: The Vaisala ceilometers CT25K and CL31 are eye-safe single lens lidar systems reporting attenuated backscatter profiles; they often operate 24 h a day in fully automated, hands-off operation mode. These profiles can be used for more than just cloud-base height determination. In dry weather situations, there is a fairly good correlation between the ceilometer near-range backscatter and in situ PM10 concentration readings. The comparison of mixing height values based on soundings and on ceilometer backscattering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
200
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(220 citation statements)
references
References 6 publications
4
200
0
1
Order By: Relevance
“…This design reduces the optical crosstalk between transmitter and receiver and in turn increases the signal-to-noise ratio. A beam splitter gives full overlap of the transmitter and receiver field of view at an altitude of 70 m (Münkel et al, 2007).…”
Section: Vaisala Cl31mentioning
confidence: 99%
See 1 more Smart Citation
“…This design reduces the optical crosstalk between transmitter and receiver and in turn increases the signal-to-noise ratio. A beam splitter gives full overlap of the transmitter and receiver field of view at an altitude of 70 m (Münkel et al, 2007).…”
Section: Vaisala Cl31mentioning
confidence: 99%
“…The CL31 ran with firmware v1.7 and noise_h2 on. For morein-depth information about the instrument see Münkel et al (2007) and Kotthaus et al (2016).…”
Section: Vaisala Cl31mentioning
confidence: 99%
“…However, it has been shown that the signal reduction due to the near-field problem can be compensated for well with the manufacturer's correction (Markowicz et al, 2008). The unique single-lens design gives full overlap of the transmitter and receiver field of view at an altitude of 0 m (Münkel et al, 2007), which allows CT25k ceilometers to obtain high signal-to-noise ratio for lidar return signals at a low altitude. The working wavelength of CT25k ceilometers is ∼ 905 nm where water vapor absorption exists (Wiegner et al, 2014;Wiegner and Gasteiger, 2015).…”
Section: Datamentioning
confidence: 99%
“…A newer version of the Vaisala Ceilometer CL31 has been used instead of the Vaisala CT25K since 2010 at the ARM SGP site. The Vaisala CL31 has the same laser system, wavelength and measurement range as CT25k but improved spatial and temporal resolution and algorithms for cloud amount and mixing layer height detection (Münkel et al, 2007). To estimate the possible response changing of the CL31 ceilometer in different years, we compared the same 3 years (2012,2013,2014) of yearly average ceilometer backscatter profiles under nighttime clear conditions as used for the CT25K.…”
Section: Test In a Different Regionmentioning
confidence: 99%
See 1 more Smart Citation